2020
DOI: 10.6115/fer.2020.032
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Family Life and Relationships during the COVID-19 Pandemic and their Associations with Perceived Stress

Abstract: This study explores how the COVID-19 pandemic has changed family life and relationships as well as how these changes affect perceived stress among married men and women. This study investigated changes in family time use, household work, child care, leisure activities, income and expenditures along with relationships between spouses and children using a sample of 627 married persons surveyed online from May 19 to 25, 2020. The results showed that the amount of time spent on household work, child care, and fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 15 publications
2
21
1
3
Order By: Relevance
“…This finding may seem inconsistent with many findings, suggesting an increase in negative parenting behaviors [ 15 , 21 , 22 , 23 , 25 , 26 ]. However, this is in line with a few findings [ 28 , 29 ], supporting the possibility that parenting styles may be considerably stable and not easily affected by temporary stressful events or changes in external circumstances. However, it is also possible that the during-COVID-19 sample in the current study was biased such that the sample more likely consisted of children having positive parent-child relationships than children from at-risk families, because children’s participation required parental consent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding may seem inconsistent with many findings, suggesting an increase in negative parenting behaviors [ 15 , 21 , 22 , 23 , 25 , 26 ]. However, this is in line with a few findings [ 28 , 29 ], supporting the possibility that parenting styles may be considerably stable and not easily affected by temporary stressful events or changes in external circumstances. However, it is also possible that the during-COVID-19 sample in the current study was biased such that the sample more likely consisted of children having positive parent-child relationships than children from at-risk families, because children’s participation required parental consent.…”
Section: Discussionsupporting
confidence: 91%
“…First, parenting style may be considerably stable, as it is defined as the values and goals that parents have in socializing their children, the parenting practices they employ, and the attitudes they express toward their children [27]. Consistent with this possibility, some studies conducted in the United Kingdom and Korea found that most parents reported no change in parent-child relationship compared to the pre-COVID-19 period [28,29].…”
Section: Children's Social Relationship During the Covid-19 Pandemicmentioning
confidence: 99%
“…The multitude of these conditions probably makes the situation particularly challenging for young children, which is hypothesized to lead to increased emotional and behavioral problems. First evidence during the COVID-19 pandemic supports this assumption [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the current study employed a longitudinal approach. Given that most research to date exploring the impact of the COVID-19 pandemic on children and families relied on cross-sectional designs [e.g., 2 , 4 , 5 ; for an exception see 6 ], little is known about the dynamic changes in the relations between child well-being and parental strain between different phases of the pandemic. Our study aimed to close this research gap.…”
Section: Introductionmentioning
confidence: 99%
“…That is, other than parental strain, which is directly affected by macrostructural changes induced by the COVID-19 pandemic, the parent–child relationship quality describes the general nature of the relationship prior to and less affected by the COVID-19 pandemic. First evidence seems to underscore this proposition as the majority of parents does not report a change in the parent–child relationship quality during the peak of the pandemic [ 5 ]. Likewise, parental self-efficacy can be conceptualized as parents’ general conviction of their child rearing competencies regardless of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%